The application of nitric oxide delivery in nanoparticle-based tumor targeting drug delivery and treatment - Qin, Lin (Asian J Pharm Sci, 2019)
Nitric oxide (NO) shows great role in tumor biology. Recent years, more and more researches utilized NO donor in tumor targeting drug delivery and treatment. In this review, we summarized the NO donors by their endogenous and exogenous stimuli. Then the application of NO donors, which was the main aim of the review, was discussed in detailed according to their functions, including inducing tumor cell apoptosis, reversing tumor multidrug resistance, inhibiting tumor metastasis and improving drug delivery.